Evaluation of Health Related Quality of Life in Dogs Treated with Chemotherapy for Lymphoma - Atanaskova Petrov Elena; Kjosevski Miroslav; Celeska Irena (Acta Veterinaria, 2023)
Lymphoma is the most common hematopoietic tumor in dogs. The standard diagnostic approach and staging includes detailed clinical history, physical examination and extended laboratory workup including lymph node cytology. Multidrug chemotherapy is the main treatment of the disease. Often, owners are concerned about the side effects of the treatment and the quality of life of their dog during chemotherapy. The aim of this study was to analyze the health related wellbeing of the patients with lymphoma previous, during and at the end of the chemotherapy. Five patients with multicentric lymphoma were monitored in three phases (beginning, middle and end of chemotherapy). The monitoring included clinical examination, laboratory analyses and a questionnaire for the owner. Results revealed significant improvement (p< 0.1) of the basic red blood cells parameters (RBC, PCV and Hb), platelets (PLT) as well as liver enzymes (ALT, AST) and protein status (total protein and globulin). Regarding the life quality assessed by the owners, dogs' appetite, general health compared to each visit and the current quality of life were significantly improved (p<0.1) and all of the owners were satisfied with the decision for chemotherapy.